2000
DOI: 10.1097/00006454-200002000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Human antibodies to pneumococcal surface protein A in health and disease

Abstract: We demonstrate for the first time the existence of antibodies to PspA in human sera in health and disease. The findings in ill children suggest that antibodies to PspA might play a role in protection against pneumococcal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 13 publications
2
26
0
1
Order By: Relevance
“…Recent studies of humans have shown that antibodies to pneumolysin, PspA, and PsaA are present in serum in healthy people and patients with invasive disease (43,48). IgA antibodies are also found in saliva in children, and patients with positive cultures from nasopharyngeal swabs or from middle ear fluid had higher antigen-specific IgA concentrations than culture-negative controls (46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies of humans have shown that antibodies to pneumolysin, PspA, and PsaA are present in serum in healthy people and patients with invasive disease (43,48). IgA antibodies are also found in saliva in children, and patients with positive cultures from nasopharyngeal swabs or from middle ear fluid had higher antigen-specific IgA concentrations than culture-negative controls (46).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies of mice have shown that immunization with these proteins can protect against infection with multiple serotypes of pneumococcus (1) and/or prevent nasopharyngeal carriage (9,10). It has been shown that pneumococcal carriage and infections induce salivary and serum antibodies to PsaA, pneumolysin, and PspA in children (43,46,48).…”
mentioning
confidence: 99%
“…Antibodies to PspA were measured using standard enzyme-linked immunosorbent assay (ELISA) methods (39,47). We used stored plasma samples instead of serum samples.…”
Section: Subjectsmentioning
confidence: 99%
“…Antibodies to PsaA, PspA and Ply have been found in human serum and mucosal secretions [12,13], emerging with age and exposure to pneumococci. Children with invasive pneumococcal infection had lower acute phase serum anti-PspA titers than controls in one study, implying a protective role for these antibodies [14]. To explore these pneumococcal protein antigens further as human vaccines, it is important to characterize naturally acquired immune responses particularly in relation to nasopharyngeal carriage of pneumococci and to investigate whether they are protective.…”
Section: Introductionmentioning
confidence: 99%